IMPLEMENTATION OF MIT APP INVENTOR IN GO REMPAH DEVELOPMENT - Rahayu Amalia; Rasmila; Chairullah; Yusriah Herawati (Informatika, Universitas Jenderal Soedirman, 2022)
Spices are one of the raw materials needed for basic ingredients for food, beverages and medicines, of which the State of Indonesia is one of the spice producers who is ranked first in the world. Spices can be found in Traditional Markets and Modern Markets, however, there has been a drastic decline in spice buyers in Traditional Markets during the current Covid-19 pandemic. This has an impact on one of the traditional markets in the city of Palembang, namely